Unconventional Anomalous Hall Effect Driven by Self‐Intercalation in Covalent 2D Magnet Cr2Te3 - Keke He; Mengying Bian; Samuel D. Seddon; Koushik Jagadish; Andrea Mucchietto; He Ren; Erik Kirstein; Reza Asadi; Jaeil Bai; Chao Yao; Sheng Pan; Jie‐Xiang Yu; et al. (Advanced Science)
Abstract Covalent 2D magnets such as Cr2Te3, which feature self‐intercalated magnetic cations located between monolayers of transition‐metal dichalcogenide material, offer a unique platform for controlling magnetic order and spin texture, enabling new potential applications for spintronic devices. Here, it is demonstrated that the unconventional anomalous Hall effect (AHE) in Cr2Te3, characterized by additional humps and dips near the coercive field in AHE hysteresis, originates from an intrinsic mechanism dictated by the self‐intercalation. This mechanism is distinctly different from previously proposed mechanisms such as topological Hall effect, or two‐channel AHE arising from spatial inhomogeneities. Crucially, multiple Weyl‐like nodes emerge in the electronic band structure due to strong spin‐orbit coupling, whose positions relative to the Fermi level is sensitively modulated by the canting angles of the self‐intercalated Cr cations. These nodes contribute strongly to the Berry curvature and AHE conductivity. This component competes with the contribution from bands that are less affected by the self‐intercalation, resulting in a sign change in AHE with temperature and the emergence of additional humps and dips. The findings provide compelling evidence for the intrinsic origin of the unconventional AHE in Cr2Te3 and further establish self‐intercalation as a control knob for engineering AHE in complex magnets.